Microdiscectomy for Lumbar Intervertebral Disc Prolapse: Is Fixation Required? - Amey P. Patankar; Shivani Chaudhary; Kashyap Patel (Indian Journal of Neurosurgery)
Introduction Microdiscectomy, as of now, is considered the gold standard for the treatment of herniated lumbar disc. It preserves motion at the spinal segment and does not alter the local spinal anatomy significantly, resulting in a “functional and mobile” spine. Development of increasingly better-quality implants has seen their indiscriminate use in cases without any demonstrable instability. We see an increasing number of patients of lumbar disc prolapse being treated by fixation and fusion procedures, without any clear indication or evidence supporting such practice. This adds to the operating time, blood loss, cost of surgery and leads to loss of motion at the spinal segment resulting in a “stiff and immobile spine.” Our 10-year experience of treating lumbar disc herniation by micro-discectomy makes a strong case for preserving the spinal motion segment wherever possible and to use fixation very judiciously only in cases of proven instability.